OPTIMALISASI GREEN HOUSE MELALUI EDUKASI PENGELOLAAN LAHAN DAN PEMBUATAN PUPUK ORGANIK CAIR (POC) UNTUK KEMANDIRIAN PANGAN DESA BATUMARTA 1 KECAMATAN LUBUK RAJA - M.Farhan Algonio; Sulia Ningsih; Edwan Vanesa; Syahran Pito Sahaji; Reynan Stevano (PT. Hasba Edukasi Mandiri, 2026)
Greenhouse optimization is a crucial strategy for supporting village food self-sufficiency by increasing agricultural productivity and sustainability. This activity, part of the Student Community Service Program (KKN), was implemented in Batumarta 1 Village, Lubuk Raja District, in response to the village's need to optimize underutilized Greenhouse facilities. The main challenges faced by the community include limited fertile land, dependence on chemical fertilizers, and the suboptimal use of local organic waste. The KKN program employed an educational and participatory approach through outreach, training, and mentoring for farmer groups and the village community. Land management education focused on sustainable soil cultivation techniques, cropping patterns, and environmentally friendly pest control in Greenhouse s. Furthermore, training was provided on the production of Liquid Organic Fertilizer (POC) using local organic materials such as kitchen waste, livestock manure, and crop residues. The results of the activity demonstrated increased community knowledge and skills in Greenhouse management and independent production of POC, which has resulted in improved land fertility, production cost efficiency, and sustainable food self-sufficiency in Batumarta 1 Village.